Local Government Administration in Nigeria and Pakistan: A Cross-Cultural Content Analysis - Sadiq, Saiqa; Usman, Abbo; Iqbal, Rana Pervaiz; Bukhari, Syed Mussawer (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper represent a modest attempt geared toward a cross-cultural comparative analysis of the local government systems in Nigeria and Pakistan with the view to diagnose and brings to limelight key areas of administrative divergences and convergences for the effectiveness and betterment of both systems. The paper is purely descriptive and content analytical in which secondary data such as journals, books and online materials were used. The results showed that the local government systems in Nigeria and Pakistan share a lot of similarities and differences in terms of their evolution, functions, political and administrative structures, organs, finances, reforms for instance, modern local governments in Nigeria and Pakistan evolved during the colonial epoch when the British government colonized both countries. The diagnosis also reveals number of encumbrances such as inadequate funding and lack of autonomy which have individually and collectively continue to constitute hindrances to the effectiveness of local democracy in both countries. The paper amongst others, recommended restructuring of local governments, giving them adequate as well as granting them an unconditional political, administrative and financial autonomy as this can revamped and strengthen the institutions thereby making them more effective in delivering local democracy.